Statybos įmonės valdymo koordinavimo sistema - Ginevičius, Romualdas (Journal of Civil Engineering and Management, 1996)
The system of management coordination at building enterprises Co-ordination of a building enterprise activities alonside with division of labour represents the second essential organizational principle. Co-ordination is performed by four methods: by personal directives, self-managing, programmes and plans. The first two of them may be applied to the feed-back co-ordination and the preliminary one, others only to the preliminary co-ordination. A system of a building enterprise activities co-ordination can be measured by a system of indices. Such system includes partial measures expressing the scale of combining the application of co-ordinating mechanisms and a generalized index which unites in a certain way the partial indices. Article in Lithuanian. First Published Online: 26 Jul 2012